2001
DOI: 10.1128/aac.45.12.3657-3659.2001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Herpes Simplex Virus Reactivation by Dipyridamole

Abstract: Herpes simplex virus (HSV) reactivation from latency was investigated. Reactivation of thymidine kinasenegative HSV, which is defective for reactivation, was greatly enhanced by thymidine (TdR). The reactivationenhancing effect of TdR was blocked by dipyridamole (DPM), a known nucleoside transport inhibitor. DPM also inhibited wild-type HSV reactivation, suggesting potential antiviral use.In experimental models of herpes simplex virus (HSV) infection, expression of viral thymidine kinase (TK) has been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…Dipyridamole is very effective at inhibiting nucleoside transport into cells, and this is the presumed mechanism for its medical efficacy. Its activity was also evaluated for other applications, including use as an inhibitor of herpes simplex virus reactivation (33) and as a potentiator of the antiviral effects of 3Јazido-3Јdeoxythymidine against human immunodeficiency virus (22 even when administered in the absence of 3Јazido-3Јdeoxythy-midine (22). Our mengovirus studies found dipyridamole to be equally effective in infected cells and in vitro replication reactions where nucleoside uptake was not an issue.…”
Section: Discussionmentioning
confidence: 86%
“…Dipyridamole is very effective at inhibiting nucleoside transport into cells, and this is the presumed mechanism for its medical efficacy. Its activity was also evaluated for other applications, including use as an inhibitor of herpes simplex virus reactivation (33) and as a potentiator of the antiviral effects of 3Јazido-3Јdeoxythymidine against human immunodeficiency virus (22 even when administered in the absence of 3Јazido-3Јdeoxythy-midine (22). Our mengovirus studies found dipyridamole to be equally effective in infected cells and in vitro replication reactions where nucleoside uptake was not an issue.…”
Section: Discussionmentioning
confidence: 86%
“…The products of alkylation of (1a,c) with α-haloacid and/or α-halo-ester such as mono-chloroacetic acid is dependent upon the reaction conditions 30 ; if the reaction is carried out in refluxing ethanol/piperidine and/or dry acetone/anhydrous potassium carbonate, the isolated products are 4-aryl-5-cyanopyrimidin-6(1H)-one-2-thioglycollic acid derivatives (9a,b), while if it done in DMF and ethanolic NaOH (10%), the products are identified as the bicyclic Downloaded by [McGill University Library] at 01:07 11 October 2012 system 6-cyano-7-aryl [1,3]thiazolo[3,2-a]pyrimidin-3,5-dione derivatives (10a,b), which are obtained also on treatment of (9a,d) with a refluxing mixture of glacial acetic acid-anhydrous AcONa. On the other hand treatment of the title compounds (1a,c) with chloroacetyl chloride 9 as bi-functional halo-organic compound in DMF afforded the same products 10a,b.…”
Section: Resultsmentioning
confidence: 99%
“…Alkylation of 1a with α-haloketones such as mono-bromoacetone 8 depends upon the reaction conditions and the used base; if the reaction is carried out in refluxing ethanol and piperidine, the obtained products are 2-substituted thio-4-(3,4-methylenedioxyphenyl)-5-cyanopyrimidin-6(1H)-ones (7), while if it done in DMF and ethanolic NaOH (10%) it yielded 3-substituted 6-cyano-7-(3,4-methylenedioxyphenyl)- [1,3]thiazolo[3,2-a]pyrimidine-5-ones (8), also compounds (7) underwent cyclization by refluxing with a mixture of acetic anhydride/pyridine (1:1) to afford (8).…”
Section: Resultsmentioning
confidence: 99%
“…On account of the pharmaceutical interest in these compounds, the development of highthroughput methodologies for the synthesis of novel pyrimidine-fused heterocyclic scaffolds is in continuous expansion. [15][16][17][18][19] It has become widely accepted that many classical reactions perform better under microwave irradiation than by conventional heating methods. [20][21][22][23][24] Microwave irradiation has been used to carry out a wide range of reactions in short times, with high yields and regioselectivity, and frequently without the need of solvents.…”
Section: Introductionmentioning
confidence: 99%